The Role of Positron Emission Tomography/Computed Tomography in the Management of Differentiated Thyroid Cancer: Current Applications and Future Perspectives - Panagiotidis, Emmanouil; Zhang-Yin, Jules Tianyu (Journal of clinical medicine, 2024)
Differentiated thyroid cancer (DTC), comprising papillary and follicular thyroid carcinoma, is the most common thyroid malignancy and typically has a favourable prognosis when detected early. Positron emission tomography/computed tomography (PET/CT) has emerged as a valuable imaging modality, integrating metabolic and anatomical data. Although PET/CT is not usually part of the initial diagnostic process due to DTC’s indolent nature and low metabolic activity, it plays an essential role in selected clinical scenarios. This includes identifying recurrence in patients with elevated thyroglobulin (Tg) levels and negative radioactive iodine (RAI) scans, evaluating metastatic disease, and guiding treatment in advanced cases. As the use of PET/CT evolves in oncology, this review explores its application in regard to staging, detection of recurrence, and follow-up in terms of managing DTC while also evaluating potential challenges that may occur in the future. The review also considers emerging radiotracers and the theragnostic potential of PET/CT.